Characterization of the phenotypic consequences of the Duffy-null genotype - Hysong, Micah R.; Shuey, Megan M.; Huffman, Jennifer E.; Auer, Paul; Reiner, Alexander; Raffield, Laura M. (Blood advances, 2025)
•rs2814778-CC is only reproducibly associated with changes in white blood cell count and not with any disease outcomes.•Race is not an accurate predictor of Duffy-null–associated benign neutropenia; genetic screening of rs2814778 is needed. [Display omitted] A wealth of research focused on African American populations has connected rs2814778-CC (“Duffy-null”) to decreased neutrophil (neutropenia) and leukocyte counts (leukopenia). Although it has been proposed that this variant is benign, prior studies have shown that the misinterpretation of Duffy-null–associated neutropenia and leukopenia can lead to unnecessary bone marrow biopsies, inequities in cytotoxic and chemotherapeutic treatment courses, underenrollment in clinical trials, and other disparities. To investigate the phenotypic correlates of Duffy-null status, we conducted a phenome-wide association study across >1400 clinical conditions in All of Us, the Vanderbilt University Medical Center’s Biobank, and the Million Veteran Program. This reveals that Duffy-null status is only reproducibly associated with changes in white blood cell count and not with any disease outcomes. Moreover, we find that Duffy-null–associated neutropenia is on average less severe than other neutropenia cases in All of Us. We also show that this genotype is present in considerable frequencies in All of Us populations that are genetically similar to African (68%) and Middle Eastern (14%) 1000 Genomes/Human Genome Diversity Project reference populations as well as those who identify with >1 race (12%), as Pacific Islander (7%), and as Hispanic (5%). Furthermore, we find that race is not an accurate predictor of Duffy-null status or associated benign neutropenia. Our research suggests that broad genetic screening of rs2814778 across all populations could provide a more robust and accurate understanding of white blood cell count and mitigate resulting health disparities.